Desarrollo del diseño del proceso de transesterificación para la producción de biodiesel a partir de la microalga Scenedesmus dimorphus empleando solventes verdes (2020)
In the present theoretical research work, the design of the transesterification process was developed from bibliographic compilations of investigations carried out with the microalgae Scenedesmus dimophus and green solvents. Initially, the culture parameters of the Scenedesmus dimorphus microalgae were established with the presentation of the pH, light, agitation and microalgal nutrition factors. Each of the determined culture parameters is of vital importance in the lipid extraction results. Similarly, for green solvents a bibliographic compilation is made with the parameters that affect the performance and the extraction of lipids. The selected parameters that were recorded in table 8 and 9 are the properties, efficiency, extraction time, cost and extraction method. From the author Jeevan and other authors. Then the parameters of the transesterification process were selected. With this, initially, a classification of lipids was carried out in MUFAS, PUFAS, SFAS, assigning factors, the factor with the highest value is the one suitable for the transesterification process. Then, once the lipid profile classification was finished, several articles related to the transesterification process were taken in order to select parameters. Those parameters selected are transesterification, moisture content, reaction time, optimum temperature, and agitation. Finally, with the selected parameters of the transesterification process, the process was designed based on an investigative work where they developed a transesterification process with microalgae. Therefore, the design is presented with a description of each of the process streams and the selected equipment.